Particle Boards Manufacturing from Bagasse Fibers - Z. OSMAN, R. ABD ALLAH, (Gezira Journal of Engineering and Applied Sciences, 2019)
This work aimed to improve the mechanical and physical properties of particle board made from Bagasse fibers by adding different ratios of Calotropis procera, CP, wood particles, underutilized bush species in Sudan. Particleboards made from Urea formaldehyde (UF) (16%) based on the oven dry weight of the fibers and CP wood particles were added to Bagasse fibers in two ratios 50% and 30%. The panels were produced using 200°C pressing temperature, 190 BAR pressure, and 7 min of pressing time with 0.65 g/cm³ target density. The produced panels were tested for their mechanical and physical properties and then evaluated using British Standards (BS EN). The results revealed that addition of 50% CP wood particle could improve the mechanical and physical properties as the best modulus of rupture (MOR) and modulus of elasticity (MOE) values (11.59N\mm 2 and 1609N\mm 2 respectively) and the lowest value of thickness swelling (TS) obtained was (22.10%) .Therefore, the panels could be used for general uses. In addition, the panels made from Bagasse only showed reduction in the mechanical and physical properties compared to those made from 30% which has MOR and (MOE) values of 9.36 N\mm 2 and1485 N\mm 2 and were lower than the values specified by BSEN standards. As for the panels made from only CP, it has MOR and MOE slightly lower than standard. All panels made from Bagasse and CP in different ratios have unique internal bond, which well exceeded the performance level specified in BSEN standards for purposes in wet and dry conditions. The study concluded that the mechanical and physical properties for the panels made from Bagasse fibers could be improved by the addition of 50% CP wood particles.